Propuesta de un nuevo pacto fiscal para fortalecer la resiliencia de las finanzas estatales en México; Proposal for a new fiscal pact to strengthen the resilience of state finances in Mexico - Laura Sour Vargas (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Mexico's fiscal response to the needs arising from the COVID-19 pandemic was among the lowest compared to other Latin American countries. This study examines the fiscal effort at the state level in Mexico over a 27-year period, using a panel database that includes all 31 states of the Republic. The results obtained through a generalized least squares model (GLS) suggest that the dependence of state governments on federal transfers is unsustainable. It is concluded that there is a need to enhance the resilience of state public finances to address the increasing local needs and unexpected challenges, such as those brought on by the COVID-19 health crisis. As a suggestion, the reconfiguration of taxes related to tourism and the introduction of specific taxes for nature-based tourism are proposed.
Keywords: H20; H39; H50; H72; H77; 330; Decentralization; fiscal effort; local governments; Mexico